Discovering of Tumor‐targeting Peptides using Bi‐functional Microarray. Issue 18 (9th November 2015) - Wang, Weizhi; Wang, Zihua; Bu, Xiangli; Li, Ren; Zhou, Mingxing; Hu, Zhiyuan
Abstract : A bi‐functional microarray for in situ peptide screening is presented herein, from which an affinity peptide towards EpCAM is screened out for tumor cell capture.